Multimodality Imaging in the Evaluation and Prognostication of Cardiac Amyloidosis - Scheel, Paul J.; Mukherjee, Monica; Hays, Allison G.; Vaishnav, Joban (Frontiers in Cardiovascular Medicine, 2022)
Abstract Cardiac amyloidosis (CA) is an infiltrative cardiomyopathy resulting from deposition of misfolded immunoglobulin light chains (AL-CA) or transthyretin (ATTR-CA) proteins in the myocardium. Survival varies between the different subtypes of amyloidosis and degree of cardiac involvement, but accurate diagnosis is essential to ensure therapeutic interventions that may slow or potentially prevent morbidity and mortality in these patients. As there are now effective treatment options for CA, identifying underlying disease pathogenesis is crucial and can be guided by multimodality imaging techniques such as echocardiography, magnetic resonance imaging, and nuclear scanning modalities. However, as use of cardiac imaging is becoming more widespread, understanding optimal applications and potential shortcomings is increasingly important. Additionally, certain imaging modalities can provide prognostic information and may affect treatment planning. In patients whom imaging remains non-diagnostic, tissue biopsy, specifically endomyocardial biopsy, continues to play an essential role and can increase diagnostic accuracy in a timely manner such that appropriate treatment can be started. In this review, we examine the multimodality imaging approach to the diagnosis of CA with particular emphasis on the prognostic utility and limitations of each imaging modality. We also discuss how imaging can guide the decision to pursue tissue biopsy for timely diagnosis of CA.